THE RELATIONSHIPS BETWEEN THE DARK TRIAD, ANOMIA, NEGATIVE AFFECTIVITY AND COUNTERPRODUCTIVE WORK BEHAVIOURS (CWBs) - Narehan Hassan; Azwan Shah Aminuddin; Abdul Kadir Othman; Mazuin Mat Halif (International Journal of Accounting, Finance and Business, 2023)
The research focused on the differences found in individual personalities that drive people to engage in CWBs, even though certain studies have achieved popularity by using methods and concentrating on specific Counterproductive Work Behaviours (CWBs). The study's independent variables included the Dark Triad—Machiavellianism, Narcissism, and Psychopathy—as well as Anomia and Negative Affectivity. Counterproductive Work Behaviours of Types S, O, and D were used as the basis for CWBs, which were used as the dependent variable. 588 respondents were included in the stratified quota sample technique, and their responses were gathered through online surveys. The results of this study showed that the variables stated above showed significant links with CWB Type S, while Narcissism, Machiavellianism, and Anomia exhibited significant relationships with CWB Type O and Type D. The results of this study should assist other academics in conducting research in this area using more variables and better understanding the subject of Counterproductive Work Behaviours (CWBs). It is advised that more research be done to consider the impact of additional employment aspects such as reward systems or job characteristics, as well as include moderating variables that could temper the link between the variables.